ISLAM AND LOCAL WISDOM: HARMONY IN THE LAND OF KARO: ISLAM DAN KEARIFAN LOKAL: HARMONI DI TANAH KARO - Fauziah Fauziah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This article discusses the dynamics of interaction between Islam and the local wisdom of the Karo people in North Sumatra, Indonesia. Tanah Karo is known for its strong customary system and distinctive social structure, but in recent decades it has also experienced the growth of the Muslim community, both from native converts and immigrants. This research aims to examine how Islam adapts and forms harmony with local culture through the process of acculturation, cultural da'wah approaches, and collaboration between religious and traditional leaders. The methods used are literature studies and qualitative analysis of socio-religious practices in the Land of Karo. The results of the study show that the success of Islam in integrating with the Karo culture lies in a non-confrontational approach, respect for local values, and the use of traditional languages and symbols in religious activities. This study confirms that Islam and local culture are not opposing entities, but can synergize in building social cohesion and harmonious diversity.